Redesigning subject guides with usability testing: a case study. - Chan, Christopher; Gu, Jennifer; Lei, Chloe (Journal of Web Librarianship)
This study considers best practices in subject guide design on the LibGuides platform based on usability tests and semi-structured interviews conducted at a mid-sized university library. The study investigated student preferences for guide navigation and was then expanded to address the overall usefulness of subject guides to students. The results indicate that the choice between side and tabbed navigation is highly individual, with students sometimes using the same reasoning to explain opposite preferences. The findings also suggest that thoughtfully maintained subject guides remain relevant to students. The authors recommend that librarians should enlist help from faculty members to promote subject guides and reconsider the inclusion and presentation of subject librarian photos in their guides. They also recommend that librarians conduct their own usability testing to ensure that their subject guides are best serving their particular institutional context.